Essential oils and their applications in agriculture and agricultural products: A literature analysis through VOSviewer. (October 2022) - Catani, Linda; Grassi, Eleonora; Cocozza di Montanara, Adele; Guidi, Loretta; Sandulli, Roberto; Manachini, Barbara; Semprucci, Federica
Abstract: In agriculture, more attention has been paid to limit the amount of chemical plant protection products. A potential alternative solution has been found in essential oils (EOs), which appear as promising candidates for their properties (safe, bioactive, biodegradable products) in managing plant diseases in agriculture. Therefore, a co-occurrence analysis was carried out on the available literature on Scopus database, through network maps created by VOSviewer software in order to identify the EOs used in agriculture, agricultural products and their target application. USA and India appeared as the most productive countries in terms of documents and citations followed by Iran and Italy. The co-occurrence analysis revealed eight, more frequently used, EOs in agriculture, in particular, they found more applications as antibacterial and insecticidal agents. On the contrary, any specific EO for nematicidal and acaricidal activity emerged from the analysis. The EOs with the largest applicability were Thymus (mainly T. vulgaris ), Citrus, Rosmarinus officinalis, Origanum, Lavandula, Mentha, Ocimum (mainly O. basilicum ). Thanks to EOs main features, is possible to invest more in the research, as demonstrated by the increasing trend of documents published in the last decades and the list of high-quality journals interested in this topic. An easier interpretation of the great amount of data enables to identify what has been investigated till nowadays to shape the potential future progression and prospective in this research field. Highlights: Potential future progression and prospectives in the research of new plant protection products (PPPs) in agriculture. Exploration in the role of essential oils (EOs) in agriculture till nowadays. The available literature on Scopus database was investigated to analyze and create network maps using VOSviewer software.